2016
DOI: 10.4028/www.scientific.net/msf.872.45
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steel Strip-Feeding Process on Density and Segregation of Casting Ingot

Abstract: The effect of steel strip-feeding ratio and superheat degree of molten steel on density and segregation of casting ingot is investigated by an original position analysis. It indicates that under the same degree of superheat condition, with the increase of feeding ratio, the average density of the casting ingot increases and the central segregation of the ingot decreases. Under the same feeding ratio conditions, the density and the central segregation increase with the increase of the degree of superheat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Zhao et al [26,27] also observed a similar increasing trend, as shown in Table 3. For large R (0.76% feeding ratio with a 50 K superheat), the equiaxed zone ratio doubled and the grain size was half of the original structure.…”
Section: Laboratory Feeding Strip Experimentssupporting
confidence: 65%
See 3 more Smart Citations
“…Zhao et al [26,27] also observed a similar increasing trend, as shown in Table 3. For large R (0.76% feeding ratio with a 50 K superheat), the equiaxed zone ratio doubled and the grain size was half of the original structure.…”
Section: Laboratory Feeding Strip Experimentssupporting
confidence: 65%
“…Pilot production [16,18] and as-cast feeding experiment [25][26][27] have already indicated that a complete melting strip (which means D s is more shallow than the liquid core depth) and an appropriate R are necessary for a satisfying slab structure. Meanwhile, Equation (4), (10), and (14) shows that many parameters affect two or three of t m , D s , and R simultaneously, including physical parameters of liquid steel and steel strip, v f , d 0 , and ΔT.…”
Section: Heat Transfer At Pseudo-steady Statementioning
confidence: 99%
See 2 more Smart Citations
“…Zhao et al [ 23 ] studied the effects of the steel strip feeding ratio and the molten steel superheat on the solidification structure and found that increasing the feeding ratio and reducing the superheat can increase the equiaxed crystal ratio and reduce the macrosegregation and porosity, which can be confirmed by using the original position analysis (OPA). [ 24 ] For the research on numerical simulation, Shen et al [ 25 ] studied the influence of steel strip feeding on the superheat degree and equiaxed grain rate by 2D slice method, and found that the superheat decreases more obviously with the increase of feeding speed, and the equiaxed grain rate also increases. However, the feeding speed should not be too fast; otherwise, it will lead to incomplete melting of the feeding strip, which is consistent with the experimental results of Isaev et al [ 21 ] Niu et al [ 26,27 ] established a mathematical model for feeding steel strips in 3D space, and studied the flow field distribution and phase transition in the mold under different feeding strip processes.…”
Section: Introductionmentioning
confidence: 99%